Necrotizing ANCA-Positive Glomerulonephritis Secondary to Culture-Negative Endocarditis - Sophie Van Haare Heijmeijer; Dunja Wilmes; Selda Aydin; Caroline Clerckx; Laura Labriola (Case Reports in Nephrology)
Infective endocarditis (IE) and small-vessel vasculitis may have similar clinical features, including glomerulonephritis. Furthermore the association between IE and ANCA positivity is well documented, making differential diagnosis between IE- and ANCA-associated vasculitis particularly difficult, especially in case of culture-negative IE. We report on one patient with glomerulonephritis secondary to culture-negative IE caused by Bartonella henselae which illustrates this diagnostic difficulty.